Peran Profitabilitas dalam Memoderasi Hubungan Ukuran Perusahaan, Likuiditas dan Leverage dengan Kualitas Laba - Suriani br. Ginting; Robinhot Gultom (Universitas Methodist Indonesia, 2026)
This study aims to determine and analyze the role of profitability in moderating the relationship between company size, liquidity, and leverage with earnings quality. The objects of this study were manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The sampling technique used was purposive sampling, resulting in a sample of 73 companies. The data testing method used in this study was the Two-Stage Approach test using a data processing application tool in the form of SmartPLS. The results showed that leverage had a significant effect on earnings quality, but company size and liquidity did not have a significant effect on earnings quality. The results of the moderation test showed that profitability was able to moderate the relationship between leverage and earnings quality but was unable to moderate the relationship between liquidity and capital structure with earnings quality.